Assessing the Relationship of Aflatoxin Exposure and Stunting in Children 6-59 Months of Age in 10 Districts of Nampula Province, Mozambique - United States. Agency for International Development (Tufts University. Tisch Library., 2021)
The aim of this study was to enumerate the serum aflatoxin B1 (AFB1) in children 6-59 months of age, and estimate its association with linear growth in these children. To accomplish this aim, the team conducted a cross-sectional study that focused on understanding the extent and level of aflatoxin exposure as measured through presence in a serum sample from children. We also studied the association between serum aflatoxin and chronic malnutrition (stunting), accounting for other risk factors. The specific objectives of this study include: 1. Assess the mean serum aflatoxin in children 6-23 months and 24-59 months of age 2. Examine differences in serum aflatoxin (mean) by age group 3. Enumerate the association between serum aflatoxin and linear growth adjusting for confounders; Report to USAID Mozambique submitted by The Feed the Future Innovation Lab for Nutrition; Work conducted by Tufts University; Universidade Lúrio; ANSA; Instituto Nacional de Saúde; Nampula Central Hospital; Instituto Nacional de Estatística; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy